Comparative Study on Clinical Manifestations Associated with Various Fore-stomach Disorders in Buffaloes - Morwal, Sandhya; Sharma, S.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Fore-stomach disorders significantly impact the health and economic productivity of buffaloes. This study analysed the clinical manifestations associated with various fore-stomach disorders in buffaloes over a one-year period. Out of 2145 screened buffaloes, 615 cases were identified with digestive disorders and out of these,107 were diagnosed with fore-stomach disorders. Clinical assessments included evaluating feed and water intake, diet changes, regurgitation, defecation patterns, and faecal characteristics. The dominant findings revealed a noticeable absence of feed intake (95.33%) and a reduced in water intake (87.85%), the change in diet played a role in this affection, particularly affecting simple indigestion (80.00%) and alkalosis (100%). A complete lack of regurgitation was observed in tympany, Simple indigestion and the condition of traumatic reticuloperitonitic were also reported in affected buffaloes. Common disorders included simple indigestion, acidosis, alkalosis, tympany, ruminal impaction, traumatic reticulo-peritonitis, traumatic pericarditis, and diaphragmatic hernia, often presenting with abnormal defecation patterns. These findings underscore the importance of dietary management and clinical monitoring in preventing and managing fore-stomach disorders in buffaloes.